2018
DOI: 10.1017/s1473550418000204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CaSO4micrograins in the context of organic matter delivery: thermochemistry and atmospheric entry

Abstract: In this paper, anhydrous calcium sulphate CaSO4 (anhydrite) is considered as a carrier material for organic matter delivery from Space to Earth. Its capability of incorporating important fractions of water, leading to different species like bassanite and gypsum, as well as organic molecules; its discovery on Mars surface and in meteorites; the capability to dissipate much energy by its chemical decomposition into solid (CaO) and gaseous (SO3) oxide, make anhydrite a very promising material in an astrobiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…These numbers are very close to the average densities of the mineral and the corresponding oxide, in all cases of study. The isothermal hypothesis is supported by the Biot number analysis: considering the temperatures and the grain radii involved in our case studies, the Biot number is much smaller than one (∼10 −4 ), so the body temperature can be considered uniform [35,36].…”
Section: Evaluation Of Delivery Scenarios Involving Wsms: Computer Momentioning
confidence: 65%
See 2 more Smart Citations
“…These numbers are very close to the average densities of the mineral and the corresponding oxide, in all cases of study. The isothermal hypothesis is supported by the Biot number analysis: considering the temperatures and the grain radii involved in our case studies, the Biot number is much smaller than one (∼10 −4 ), so the body temperature can be considered uniform [35,36].…”
Section: Evaluation Of Delivery Scenarios Involving Wsms: Computer Momentioning
confidence: 65%
“…When CO 2 is completely evaporated and the grain becomes pure oxide, the grain mass does not change anymore and the temperature increases dramatically, only mitigated by blackbody radiation [34,35]. On the other hand, a sulphate micrograin can survive the atmospheric entry with a partial decomposition [36].…”
Section: Evaluation Of Delivery Scenarios Involving Wsms: Computer Momentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the computer models employed in the context of astrobiology describe phenomena either on an atomic scale (in the order of nanometres) or on a geochemical scale (in the order of hundreds of kilometres). Our group has been working for some years on astrobiological simulations, on a scale that has so far been little considered: the order of tens or hundreds of microns (Micca Longo and Longo, 2017; Micca Longo and Longo, 2018; Micca Longo et al ., 2019). At this scale, the phenomena described might be accessible to a microscope.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called delivery, that is, the actual transport of molecules from space to Earth, represents the key point of the Panspermia theory [ 7 , 8 , 9 , 10 , 11 ]. It was demonstrated that carbonate and sulfate micrometeoroids (especially calcite and anhydrite) may act as good prebiotic molecule carriers [ 12 , 13 , 14 ], in view of the well-known association between carbonates/sulfates and organic matter presence [ 15 , 16 , 17 , 18 ]. Recently, the role of the chemical composition of the primordial atmosphere was pointed out, in the context of the atmospheric entry of the aforementioned carbonate and sulfate micrometeoroids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%